Consumer buying behaviour of security, trust, privacy and delivery on online shopping in Malaysia - Keshiini, Pithaih (2024)
This study explores the critical factors influencing consumer buying behavior in the context of online shopping among adults in their 20s in Malaysia, focusing specifically on the roles of security, trust, privacy, and delivery. With the rapid expansion of e-commerce, especially highlighted during the COVID-19 pandemic, understanding the nuances of consumer behavior has become paramount for online retailers. Utilizing a quantitative research design, the study distributed 250 questionnaires, with 100 responses deemed valid for analysis. The findings indicate significant relationships between consumer buying behavior and the factors of security, trust, and delivery, highlighting their crucial role in shaping online shopping experiences. However, privacy did not show a significant direct relationship with consumer buying behavior. These insights provide valuable implications for online retailers aiming to enhance consumer satisfaction and loyalty by prioritizing these critical factors. The study contributes to the existing literature on online consumer behavior and suggests avenues for future research to further understand the dynamics of e-commerce in Malaysia.